Exploration of Counselors’ Epistemology: Epistemic Style Perspectives in Helping Relationships - Utami, Muty Rachmadiny; Utami, Nissa Aulia Belistiana; Budiman, Nandang (Jurnal Kajian Bimbingan dan Konseling, 2025)
Epistemological studies provide important insights into how counselors build their knowledge related to the helping relationship through epistemic styles. This study aims to describe the epistemology of the helping relationship in counseling. A qualitative approach with a case study design was used to explore the experiences of guidance and counseling teachers and students as research participants. Data were collected through the analysis of counseling documents and semi-structured interviews with guidance and counseling teachers as well as five counselee participants. The study results discuss the epistemology of the helping relationship of counselors in seven themes: sources of counselor knowledge, the process of constructing counselor knowledge, validation of knowledge in counseling practice, the relationship within counseling, the influence of context on knowledge, implications of knowledge for practice, and ongoing evaluation and learning. The research findings highlight the epistemology of counselors in three epistemic style perspectives: rationalism, empiricism, and metaphorism, which, in their implementation, are relevant to the counseling process.